Pamięć społeczna i polityka historyczna w programach polskich partii politycznych - Olszewski, Edward (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The transformation of the political system in Poland after the negotiations of the‘Round Table’ resulted in an increased interest in modern history, accompanied by a desire to reckon with the past, in particular with the period of communist rule after 1944. Since the 1990s, government authorities and political parties have made a natural move to legitimize the democratic political system in the area of social memory and historical policy. This process has been initiated by constitutional changes, coupled with a truly spontaneous social movement to change national symbols, names of streets and squares, patrons of schools and universities, institutions and manufacturing plants rooted in the overthrown system of communist Poland. The humanities, in particular historiography, have taken steps to reassess attitudes to Polish and global history. The issues of social memory, national identity and historical policy have been reflected in the ideologies and platforms of various political parties. The issue of social (national) memory has become entangled in political disputes and a struggle for ‘control of the past’, of interpretations of history, the value of patriotism and, by extension, of the electorate, has been waged mainly by the Law and Justice (PiS), Civic Platform (PO), and the Democratic Left Alliance (SLD) parties. This paper analyzes and describes the most influential political movements in Poland in the early 21st century as regards their attitude to collective memory and the concept of historical policy. These attitudes are presented in terms of the conservative, liberal, critical and totalitarian ‘models of historical policy’. The study implies that the conservative and liberal models predominate, clearly influenced by the ideology of Christian democracy and national tendencies. The attitude of conservative parties in particular is characterized by disrespect for academic findings and interpretations of history, a frequently ad hoc approach to facts and assessments of the past, which follows from a desire to find the in-depth historical legitimization of the status of a given party in society and to dominate the electorate.